Bioleaching of copper concentrate and pyrite by using native bacterium Acidithiobacillus ferrooxidans IRL.8F and evaluating the LPS role in bioleaching process (Global Journal of Science Frontier Research, 2012)
This study was performed to evaluate the ability of native bacterium to extract copper and iron from their ores. This bacterium was isolated from iron mineral springs in Iran's Larzan region and was named Acidithiobacillus ferrooxidans IRL.8F based on morphological and physiological characteristics and 16S rRNA molecular analyses. The results from bioleaching of copper concentrate showed that the amount of extracted copper and iron was 71.4% and 29.3%, respectively. Furthermore, in comparison with control samples, these amounts increased by 93.5% and 92%, respectively. In the control samples minor amount of metals were extracted due to spontaneous leaching. To assess the importance of bacterial lipopolysaccharydes(LPS) role, LPS of bacterium was removed. When ethylenediaminetetraacetic acid (EDTA) in concentrations of 5 and 10% was used during the bioleaching process of pyrite, process efficiency decreased to 61 and 70%, respectively. The cells lacking LPS were led to 59.4 % decrease in the amount of bacterial leaching, in contrast to whole cells. Therefore, it can be concluded that: 1. EDTA causes a drastic reduction in the efficiency of leaching process, 2. Bacterial LPS have a key role in attachment to particles of ore and 3.This bacterium is capable of leaching metals through the direct mechanism.
Keywords: Bioleaching; LPS; Ore; Copper; Pyrite